2015
DOI: 10.3390/app5030294
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic Nanofluid Hydrothermal Treatment in an Enclosure with Sinusoidal Upper Wall

Abstract: Abstract:The influence of non-uniform electric filed on Fe3O4-Ethylene glycol nanofluid hydrothermal treatment in an enclosure with sinusoidal upper and moving lower walls is investigated in this study. Control Volume based Finite Element Method (CVFEM) is utilized to simulate in the presented model. Numerical investigation are conducted for the sundry parameters such as Reynolds number; nanoparticle volume fraction and supplied. Results show that supplied voltage can change the flow shape. Coulomb force cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…However the models described in [25]- [30] ignored the peristaltic effect. Recently however several authors have considered electro-kinetic peristaltic transport, extending the earlier work of Chakraborty [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the models described in [25]- [30] ignored the peristaltic effect. Recently however several authors have considered electro-kinetic peristaltic transport, extending the earlier work of Chakraborty [24].…”
Section: Introductionmentioning
confidence: 99%
“…Mohammadi et al [29] reported very recently on hydrodynamic and direct-current insulator-based dielectrophoresis (H-DC-iDEP) microfluidic blood plasma separation. Sheikholeslami and Ellahi [30] studied transport in electrohydrodynamic nanofluids with sinusoidal upper wall and hydrothermal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ellahi [15] studied the effects of MHD and temperature-dependent viscosity on the flow of a non-Newtonian nanofluid in a pipe, while an analysis of the flow and heat transfer of water and ethylene glycol-based Cu nanoparticles between two parallel disks with suction/injection effects, has been provided by Rizwan Ul Haq et al [16]. Of course, the list of such studies can continue, but we close it with some of the most interesting analytical and numerical results that have been obtained in [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers used the Buongiorno's model to analyze the flow of nanofluids in various geometries. Some relevant studies can be seen in [27][28][29][30] and the references therein.…”
Section: Introductionmentioning
confidence: 99%